PTH-039 Prevalence of sessile serrated adenomas/polyps in distal colon during screening colonoscopy/flexible sigmoidoscopy: a single bowel cancer screening experience from uk. (17th June 2017) - Rameshshanker, R; Purchiaroni, F; Ana, W; Thomas-Gibson, S; Rajendran, A; Saunders, BP; Tsiamoulos, Z
Abstract : Introduction: Sessile Serrated Adenomas/Polyps (SSA/P) are responsible for nearly 20% of colo rectal cancer (CRC). Despite the utility of novel image enhancing techniques including narrow band imaging it is difficult to differentiate hyperplastic (HP) polyps from SSA/Ps. Vast proportion of endoscopists leave the diminutive and possibly small HP polyps in situ in the recto sigmoid area (diagnose and disregard approach). Hence there is a possibility of leaving SSA/P in the recto sigmoid region which could potentially lead to CRC later in life. Aim: To estimate the prevalence of SSA/P in recto sigmoid colon at screening colonoscopy and flexible sigmoidoscopy (FS). Method: Patients aged >55 years underwent a screening colonoscopy (n=500) or a flexible sigmoidoscopy (n=500) at our institution between August 2014 and April 2015 were included. Data collected from 500 consecutive patients who underwent a colonoscopy or a FS. Demographic, procedural and polyp data were retrieved from our endoscopy database. Results: 99.6% of (498/500) colonoscopy and 97.6% of flexible sigmoidoscopy procedures were completed. Screening colonoscopy detected 1006 polyps and FS detected 249 polyps. Polyp size ranged between 1–80 mm (colonoscopy mean size 6 mm, SD 7.2 mm; FS mean 3.4 mm, SD 3.9 mm). While colonoscopy detected 43 SSA/Ps (4.3%), FS detected only 6 SSA/Ps (2.4%) which equates to an overall prevalence of 3.9% (49/1255). Image 1 summarises the SSA/Ps prevalence by colonic segment. In recto sigmoid there were 21 SSA/Ps detected and resected which equals to a 3.9% of all recto sigmoid polyps. All SSA/Ps detected in this segment were less than 10 mm in size (range 2–10 mm). Only one of the SSA/P had dysplasia (4.7%). Prevalence of SSA/Ps in proximal colon was 4.8%. Conclusion: Our cohort showed a slightly higher prevalence of SSA/Ps in rectum and sigmoid colon. Therefore, it becomes clinically relevant to differentiate SSA/Ps from HP polyps in recto sigmoid before adapting a diagnose and disregard approach for small (<9 mm) hyperplastic looking polyps in this location. Disclosure of Interest: None Declared